Dr. INFLUENCE OF JOB BURNOUT ON INTENTION TO QUIT AMONG HEALTH SERVICE EMPLOYEES IN SOUTHWESTERN NIGERIA - Adewa, Kehinde; Tosin-Amos, Aderonke; Ilori, Taiwo Adeola (Advances in Social Sciences Research Journal, 2021)
This paper examined the influence of job burnout on intention to quit among health service employees in Southwestern Nigeria because there has been limited attention on the influence of job burnout on intention to quit. The study population is 18,295. A sample of 380 respondents were obtained using Yamane formula. Questionnaire was administered to Nurses, Administrators, Doctors, Technologists and Pharmacists with full employment status. Data was analysed with the use of Multiple regression aided by Path Analysis. The study revealed that job burnout significantly affect intention to quit. Emotional Exhaustion (t = 3.126, p < 0.05); Depersonalization (t = 0.930, p < 0.05); Personal Accomplishment (t = 1.773, p < 0.05). The study concluded that job burnout affects intention to quit among health service employees in Southwestern Nigeria. Keywords: Job Burnout, Employment Alternative, Professional Commitment, and Social Support.